Deskripsi Tentang Iman Yang Memindahkan Gunung Menurut Perspektif Alkitab Matius 17:20 - Gideon Ricu Sele (Sabda: Jurnal Teologi Kristen, 2020)
My righteous people will live by faith. Because without faith it is impossible to please God, because faith is the basis and evidence. Every believer must be able to practice his faith in everyday life. Faith as big as a mustard seed can move mountains. Quality faith is faith that has power. True faith is in accordance with the will of God which comes from God. Active faith. Faith without doubt. Faith that is completely surrendered to God without hesitation. What is the description of that mountain-moving faith? The author uses a qualitative descriptive study method from literature / literature sources that support this writing. Hopefully the results of this research can help every believer / Christian to be able to properly actualize his faith in this pluralistic society. Christians or believers can account for their faith appropriately and rightly before this world.